Pengaruh Literasi Perpajakan, Sanksi Pajak, dan Digitalisasi Sistem Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi pada KPP Pratama Singaraja - Saputra, Komang Trisnawa; Darmawan, Nyoman Ari Surya; Putra, Putu Yunartha Pradnyana (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to examine the influence of tax literacy, tax sanctions, and the digitalization of the tax system on individual taxpayers' compliance. This research is classified as quantitative research. The sample consisted of 131 non-employee individual taxpayers who are registered at the KPP Pratama Singaraja and run a business in the city of Singaraja, selected using a purposive sampling technique. The data analysis technique employed was multiple linear regression. The results indicate that tax literacy has a significant positive effect on individual taxpayer compliance. Tax sanctions also have a significant positive effect on individual taxpayer compliance. Furthermore, the digitalization of the tax system significantly and positively affects individual taxpayer compliance. These findings support attribution theory, which suggests that individuals perceive others’ behavior as influenced by both internal and external factors. Future research is recommended to explore other variables such as tax awareness, attitudes toward taxation, experiences with the tax system, social support, and the quality of tax services. Keywords : tax literacy; tax sanctions; tax system digitalization, taxpayer cmpliance